Auswirkungen der Digitalisierung industrieller Arbeit auf die berufliche und allgemeine Bildung - Berisha-Gawlowski, Angelina; Caruso, Carina; Goller, Michael; Harteis, Christian (Digitalisierung am Übergang Schule Beruf: Ansätze und Perspektiven in Arbeitsdomänen und beruflicher Förderung)
Keywords: Arbeitsmarktförderung; Arbeitswelt; Arbeitswelt - Strukturwandel; Benachteiligte

Auswirkungen der Digitalisierung industrieller Arbeit auf die allgemeine und berufliche Bildung - Berisha-Gawlowski, Angelina; Caruso, Carina; Goller, Michael; Harteis, Christian (Digitalisierung und Berufsbildung 4.0 am Übergang Schule - Beruf)

Supporting learning at work in an era of digitalization of work - Harteis, Christian (Work-based learning as a pathway to competence-based education)

Finnish and German student teachers’ motivations for choosing teaching as a career. The first application of the FIT-Choice scale in Finland - Goller, Michael; Ursin, Jani; Vähäsantanen, Katja; Festner, Dagmar; Harteis, Christian (Teaching and Teacher Education)

Die Auswirkungen der Digitalisierung auf die Bedeutung beruflicher Qualifikation aus betrieblicher Sicht - Harteis, Christian; Goller, Michael; Fischer, Christoph (Beruf, Beruflichkeit, Employability)

Becoming a Nurse Aide: An Investigation of an Existing Workplace Curriculum in a Nursing Home - Goller, Michael; Steffen, Bianca; Harteis, Christian (Vocations and Learning)

Individual and social influences on professional learning. Supporting the acquisition and maintenance of expertise. - Gruber, Hans; Harteis, Christian

The impact of digitalization in the workplace: an educational view

Machines, Change and Work: An Educational View on the Digitalization of Work - Harteis, Christian (The Impact of Digitalization in the Workplace)

Developing Occupational Expertise through Everyday Work Activities and Interactions - Billett, Stephen; Harteis, Christian; Gruber, Hans (The Cambridge Handbook of Expertise and Expert Performance)

Monitoring für die Bahnhofsmissionen: Ein datengestütztes Instrument zur Organisationsentwicklung. Projektbeschreibung und Ergebnisdarstellung - Goller, Michael
Keywords: Bahnhofsmission; Survey Feedback; Monitoring

Individual and Social Influences on Professional Learning - Gruber, Hans; Harteis, Christian

Do we betray errors beforehand? The use of eye tracking, automated face recognition and computer algorithms to analyse learning from errors. - Harteis, Christian; Fischer, Christoph; Töniges, Torben; Wrede, Britta (Frontline Learning Research)

The journey to proficiency: Exploring new objective methodologies to capture the process of learning and professional development. - Harteis, Christian; Kok, Elen; Jarodzka, Halszka (Frontline Learning Research)

Becoming a Nurse Aide: An Investigation of an Existing Workplace Curriculum in a Nursing Home - Goller, Michael; Steffen, Bianca; Harteis, Christian (Vocations and Learning)

Human agency at work: An active approach towards expertise development - Goller, Michael
Michael Goller gives a structured overview of the current discourses of human agency in relation to professional learning and development. Based on this discussion, the author develops a theoretical framework including human agency as an individual feature (i. e., a disposition) as well as a set of self-initiated and goal-directed behaviours that are assumed to affect employees’ learning and development (e. g., crafting of new work experiences). He then further specifies this theoretical framework and investigates it empirically in the domain of geriatric care nursing. Based on the findings of the three empirical studies conducted, the author discusses the relevance of human agency for the development of professional expertise of geriatric care nurses. The work received the American Educational Research Association (AERA) Workplace Learning SIG 2017 Dissertation of the Year Award.
Keywords: Workplace learning; Agency; Expertise

Intuition as Crucial Component of Professional Competence: Its Relevance for Competence-based Vocational and Professional Education and Training - Harteis, Christian (Competence-based Vocational and Professional Education)

Emotions, coping and learning in error situations in the workplace - Rausch, Andreas; Seifried, Jürgen; Harteis, Christian (Journal of Workplace Learning)

Human agency at work: Towards a clarification and operationalisation of the concept - Goller, Michael; Harteis, Christian (Agency at Work)

Learning from errors in workplace settings - Harteis, Christian; Gartmeier, Martin (Journal of Workplace Learning)